The Impact of The Use of Educational Platforms on The Attitudes of Students of The College of Basic Education in The Subject Of Mathmatics (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the research is to identify the attitudes of the students of the three experimental research groups: the first experimental group using the Classroom Google educational platform, the second experimental group using the Edmodo educational platform, and the third using the Easyclass platform (Educational trend towards the use of educational platforms, in the College of Basic Education).    As to achieve the objectives of the research, the researcher adopted a quasi-experimental design with a pre and post scale, and the research experience was applied in the academic year (2020/2021), and over an entire semester with two lectures per week, where The first experimental group, consisting of (44) male and female students, was taught using the educational platform (Google Classroom), the second experimental group using the educational platform (Edmodo), and the third experimental group using the educational platform (Easyclass).   After building the trend scale tool for using educational platforms After completing the teaching of the scientific material and applying the scale before and after, the data were processed statistically by Statistical package for social sciences version (spss-26), which showed that there were statistically significant differences in favor of the second experimental group with the largest arithmetic mean in the trend scale, and it became clear that there is a statistically significant difference between the two tests (pre and post) using the (Google Classroom) platform and in favor of the test The post test in the attitude scale, and there is a statistically significant difference between the two tests (pre and post) using the (Edmodo) platform, and in the interest of the post test in the attitude scale, there is no statistically significant difference between the two tests (pre and post) using the (Easyclass) platform in the attitude scale.